Measuring what matters: indicators of social innovativeness on the national level - Krlev, Gorgi; Bund, Eva; Mildenberger, Georg (Information systems management, 2014)
This article presents an approach to measuring social innovation. Indicators emerge from: (1) the development of a theoretically grounded measurement model, (2) a systematic review of 30 established measurement approaches. The article serves three purposes: First, it develops the conceptual understanding for social innovation. Second, through operationalization it strengthens the link between theory and empirical phenomena. Third, it paves ground for national or regional measurement of social innovation and is thus, relevant to policy making.
Gesehen am 25.09.2020